"Reclaiming My Time" Amid Organizational Change: A Dialectical Approach to Support the Thriving and Career Development for Faculty at the Margins. Issue 1 (February 2020) - Davis, Tiffany J.; Greer, Tomika W.; Sisco, Stephanie; Collins, Joshua C.
The Problem: The faculty in academia is slowly diversifying, yet individuals who identify as women, people of Color, and/or LGBTQ (lesbian, gay, bisexual, transgender, and queer/questioning) remain underrepresented. Racism, sexism, and heterosexism in the workplace, and intersections of identity and academic rank frequently marginalize women, people of Color, and LGBTQ faculty in the academy. The Solution: Critical Human Resource Development (CHRD) offers the conceptual tools necessary for institutions of higher education to engage in meaningful disruption to benefit faculty on the margins. In this article, the authors provide recommendations for organizational and systemic changes that can create new space and opportunities for marginalized faculty. The Stakeholders: The recommendations offered herein can aid academic leaders including department chairs, centers for faculty development, and faculty that have the potential to transform institutional cultures and climates.